Photodynamic Therapy for Oral Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis - Jiao Lin; Guangcheng Ni; Tingting Ding; Shangxue Lei; Liang Zhong; Na Liu; Keran Pan; Ting Chen; Xin Zeng; Hao Xu; Taiwen Li; Hongxia Dan (International Journal of Photoenergy)
To assess the efficacy of photodynamic therapy (PDT) for oral squamous cell carcinoma (OSCC), literature on this topic from Embase, PubMed, and Web of Science were obtained and analyzed. The response and recurrence rates with 95% confidence intervals (CI) were calculated using the DerSimonia–Laird method. The pooled complete response (CR) rate from the included studies was 0.799 (95% CI: 0.708–0.867), while the overall response (OR) rate was 0.967 (95% CI: 0.902–0.989). The recurrence rate (RR) was 0.158 (95% CI: 0.090–0.264). A subgroup analysis of lesion site, photosensitizer, laser type, radiant exposure, and power density revealed no statistically significant differences. In general, PDT is effective for the treatment of early OSCC. Investigations on the influence of PDT on the survival of OSCC patients, optimization of the treatment regimen, and evaluation of response after treatment are still needed.